Summer rainstorm associated with a debris flow in the Amarilla gully affecting the international Agua Negra Pass (30200S), Argentina - Lauro, Carolina; Moreiras, Stella Maris; Junquera Torrado, Sebastian; Vergara Dal Pont, Iván Pablo; Toural Dapoza, Rafael; Johannes Wolf; Tutzer Ruben (Environmental Earth Sciences)
The Central-West region of Argentina was seriously affected by a series of convective summer storms on January–February of 2013 generating many debris flows and rockfall in the Central Andes mountain regions. In particular, the unreported 8th February event caused the sad death of a 10-year-old child being completely ignored by society and local authorities. Despite this, meteorological conditions associated with this event and further episodes were rarely measured and determined mainly due to scarce meteorological stations in Andean mountain areas. In this paper, meteorological data from CMORPH algorithm and measurements of surrounding gauges were analyzed for estimating the triggering precipitation value of this event. As well, the particular debris flow channeled into the main branch of the Amarilla gully in the Agua Negra valley was geomorphologically described. The amount of precipitation associated with this debris flow was 5.5 and 13.2 mm accumulated previous to the event. This violent debris flow was generated in a talus zone in a periglacial environment located just below a covered rock glacier. However, the influence of the permafrost thawing in this process is not feasible. The altitude of the 0 °C isotherm was lower during the previous days of the event, and no monitoring on permafrost is available for this area. The volume of removed mass was estimated in 5 × 104 m3, and the mean velocity was 35 km/h. Boulders of 4 m diameter were found in the source area, while the deposit is up to 75% sandy with clasts that hardly exceed 10 cm in the alluvial fan distal part. Herein the main objective is to advice about the probable catastrophic impact of similar events in the future. These findings could be useful for hazard remediation, mitigation, and prevention plans for the Agua Negra international pass under construction. Fil: Lauro, Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias ...